ALTERNATIVE DIGITAL PROMOTION AT W BALI - SEMINYAK - Ni Luh Cahaya Erani; Budi Susanto; I Dewa Gede Ari Pemayun (Politeknik Negeri Bali, 2020)
This research is conducted to find out the application of online promotion strategy to increase room occupancy at W Bali – Seminyak because in the last three years, there was a fluctuation of room occupancy especially made by online booking source. The research objectives are to formulate promotional strategy of W Bali – Seminyak, prioritizing online promotion that can be applied by the hotel to achieve the occupancy target. The method used in this research are participant observation, interview, questionnaire and documentation with 7 key informants from sales and marketing department. The data in this research is analyzed by using the combination of qualitative and quantitative analysis; IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), IE (Internal-External) Matrix, SWOT (Strengths Weaknesses Opportunities Threats) and QSPM (Quantitative Strategic Planning Matrix).The results of IFAS matrix shows; the major strength is the hotel provides complete information at hotel website, social media, brochure, magazine and newspaper meanwhile the weakness is the hotel does not have their own magazine. The EFAS matrix shows if one of the opportunities is level of safety in Bali relative conducive and the threats is many similar hotels around Seminyak area which offer lower price. The SWOT analysis gives 8 alternative online promotions with the highest TAS (Total Attractive Score) is 99,32. Thus, the main strategy recommended is developing special package with affordable price in low season. The study results are expected can be used by managements to develop the online promotion strategy theoretically and enrich the reference especially on promotion strategy.